Status of manure generation and management practice in household pig farming in Ha Hoa district, Phu Tho province, Viet Nam - Pham Thi Mai Thao,; Ho Huong Thao, (Vietnam Journal of Science and Technology, 2018)
To assess the status of manure generation and management practice in household pig farming, the research was implemented in Ha Hoa district, Phu Tho Province. The used research methods were field survey, direct interview with households, experiment establishment to determine daily manure discharged from the different types of pigs (sow, porker, immature pig and piglet). Results showed that the average amount of manure generated per pig was 0.99 kg/day including piglets and 1.3 kg/day excluding piglets. The total amount of pig manure generated in the whole district was 80.7 tons/day. At the scale under 30 pigs, the ratio of pig farming households had waste treatment system to be 16%, partial treatment system to be 46% and not treatment system to be 38%; At the scale larger than 30 pigs, the ratio of pig farming households had waste treatment system to be 76%, partial waste treatment system to be 21% and not waste treatment to be 3%. In the whole survey area, the ratio of pig farming households had with, without and partial manure treatment system to be 46%, 21% and 33%, respectively. The study also suggested suitable solutions for pig waste management especially suitable technical solutions for different scale of pig farms in Ha Hoa district, Phu Tho province.